Color polarizing sheet and method for manufacturing the same, and use thereof
Patent Information
- Application Number
- CN202611268355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-23
AI Technical Summary
虽然该方法能制备出色彩鲜艳的偏光片,但其工艺流程极其繁琐,涉及大量的水洗、染色、清洗步骤,不仅生产效率低,而且会产生大量的染色废液和清洗废液,环保处理成本高昂
一、本发明中,提出一种彩色偏光片及其制备方法,通过选用二色性染料体系,能够精确控制偏光片的吸收波段。产品可在特定波长范围内实现高偏振度(>99%),同时保持其他波段的高透过率。相较于传统的层叠调色膜方法,本发明的制备的彩色偏光片减少了光的吸收损耗,显著提高了整体透光率和光的利用效率,尤其适用于需要特定光谱截止或增透的光学系统。
Smart Images

Figure CN122962712A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical thin film technology, specifically to a color polarizer, its preparation method, and its applications. More specifically, it relates to a technique for preparing a color polarizer using melt extrusion or wet dyeing processes, and the application of this color polarizer in display devices, optical instruments, and goggles. Background Technology
[0002] A polarizer is a thin film that allows light vibrating in a specific direction to pass through, while almost blocking light vibrating in other directions. Its core function is to convert natural light into polarized light. With the rapid development of optoelectronic display technology, polarizers have been widely used in LCD displays, OLED displays, polarized sunglasses, and 3D glasses.
[0003] In recent years, with the continuous expansion of application scenarios, the use environment of polarizers has extended from conventional indoor environments to precision fields such as outdoor LCD TVs, automotive industrial control systems, projectors, outdoor testing instruments, marine instruments, and medical equipment. In these application scenarios, products often need to withstand harsh environments such as high temperature, high humidity, and strong light exposure. Therefore, the market's performance requirements for polarizers have expanded from conventional display needs to high standards such as strong weather resistance, diverse colors, adjustable thickness specifications, and optical control in specific wavelength bands.
[0004] To meet market demand for color polarizers, existing technologies typically employ the following manufacturing methods: One method is the lamination method. This method typically involves laminating different colored films onto a conventional iodine-based polarizer, or mixing dyes into the adhesive to achieve color matching. However, the colored polarizer prepared by this method has many film layers, resulting in multiple reflections and absorptions of light as it passes through the interfaces between layers. This leads to low overall transmittance and insufficient light utilization. Furthermore, the multilayer structure is prone to problems such as interlayer delamination and blistering under high temperature and humidity environments, exhibiting poor weather resistance.
[0005] The second method is wet dyeing. This method involves washing and swelling a polyvinyl alcohol (PVA) base film, then immersing it in a solution containing dichroic dyes for dyeing, followed by cross-linking, stretching, and cleaning. While this method can produce brightly colored polarizing films, its process is extremely complex, involving numerous washing, dyeing, and cleaning steps. This results in low production efficiency and generates large amounts of dyeing and cleaning wastewater, leading to high environmental treatment costs. Furthermore, the wet process makes it difficult to control the film thickness, hindering the stable production of ultra-thin or thick polarizing sheets, thus limiting the product's application range.
[0006] Thirdly, there are limitations in the application of traditional iodine-based polarizers. Although the mainstream iodine-based polarizers currently available have high polarization, iodine itself is highly susceptible to sublimation or redox reactions under high temperature and humidity conditions, leading to problems such as fading, decreased polarization, and even failure. This makes it difficult to directly apply traditional iodine-based polarizers to fields with extremely high durability requirements, such as automotive displays or outdoor instruments.
[0007] In summary, existing color polarizer manufacturing technologies generally suffer from problems such as complex processes, significant environmental pollution, narrow thickness adjustment range, insufficient weather resistance, and low light utilization.
[0008] Therefore, there is an urgent need to develop a simple, environmentally friendly, thickness-adjustable, and weather-resistant color polarizer manufacturing technology to meet the growing demand for high-end applications. Summary of the Invention
[0009] The purpose of this invention is to solve the above-mentioned technical problems and to propose a color polarizer, its preparation method, and its application.
[0010] This invention is achieved through the following technical solution: A color polarizer, wherein the polarizer comprises at least one color polarizing functional layer; The color polarizing functional layer is composed of a resin substrate and a dichroic dye incorporated therein; The dichroic dyes are oriented in a specific direction in the resin substrate, so that the color polarizer has polarization properties in a specific absorption band. The resin substrate is selected from at least one of the following: polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), cellulose triacetate (TAC), polypropylene (PP), cyclic olefin polymer (COP), polyethylene terephthalate (PET), polycarbonate (PC), amorphous polyethylene terephthalate (APET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene terephthalate-1,4-cyclohexanediol (PETG), polyethylene terephthalate-1,4-cyclohexanediol (PCTG), cyclic olefin copolymer (COC), polyacrylate (PA), polystyrene (PS), polyethersulfone (PES), polyethylene (PE), thermosetting thiourethane, polyurethane (PU), thermoplastic polyurethane (TPU), silicone resin, and modified epoxy resin.
[0011] Furthermore, the dichroic dye is dispersed in the resin substrate by melt mixing to form a single-layer or double-layer composite colored polarizing layer.
[0012] Furthermore, the resin substrate is polycarbonate (PC) with a melt flow index (MFR) greater than 15 g / 10 min and a glass transition temperature of 120~145℃; the color polarizing functional layer is a single-layer structure, and the polarizer shows no bubbles, no delamination, and no fading failure after aging at 85℃ and 85%RH for 1000 h.
[0013] Furthermore, the resin substrate is polyethylene terephthalate-1,4-cyclohexanediol ester (PETG), with a glass transition temperature of 75~85℃; the color polarizing functional layer is formed at a low-temperature processing temperature of 180~220℃ to reduce dye decomposition.
[0014] Furthermore, the color polarizing layer includes a color-correcting protective layer and an iodine-based polarizing layer stacked together; The resin substrate of the color-tone protective layer is polymethyl methacrylate (PMMA). The resin substrate of the iodine-based polarizing layer is polyvinyl alcohol (PVA). The absolute value of the difference between the refractive index of the PMMA resin and the refractive index of the PVA resin is within 0.01.
[0015] Furthermore, the dichroic dye is incorporated into the resin substrate through impregnation and adsorption; the resin substrate is polyvinyl alcohol (PVA), and the colored polarizing layer is cross-linked with boric acid.
[0016] A method for preparing a color polarizer as described above includes the following steps: I. Provide resin substrate; II. Incorporating dichroic dyes into the resin substrate; III. The resin substrate containing the dichroic dye is stretched to align the dichroic dyes and obtain a color polarizer.
[0017] Furthermore, in step II, the step of bonding the dichroic dye to the resin substrate is performed using a melt extrusion process: The resin is melt-mixed with dichroic dye, dispersant, and antioxidant, and then co-extruded through an extrusion die to obtain an unstretched film. The stretching process employs a dry stretching method, which involves stretching in a hot air medium with a stretching ratio of 4 to 7 times.
[0018] Furthermore, when the resin substrate is polycarbonate (PC), the melt temperature gradient is set to 210~250℃ and the stretching temperature is 130~160℃. When the resin substrate is polyethylene terephthalate-1,4-cyclohexanediethanol ester (PETG), the melt temperature gradient is set to 180~220℃ and the stretching temperature is 100~130℃.
[0019] Furthermore, when the resin substrate includes polymethyl methacrylate (PMMA) and polyvinyl alcohol (PVA), a multi-channel co-extrusion die is used to co-extrude the tinted PMMA protective layer melt, the iodine-based PVA polarizing layer melt, and the PMMA protective layer melt to form a layered structure.
[0020] Furthermore, the step of bonding the dichroic dye to the resin substrate employs a wet dyeing process: The resin substrate is polyvinyl alcohol (PVA). After the polyvinyl alcohol (PVA) substrate is washed with water and swelled in sequence, it is immersed in a dyeing solution containing dichroic dyes for dyeing. After staining, a cross-linking treatment is performed, wherein the cross-linking solution used in the cross-linking treatment contains 1.0~8.0% boric acid; The stretching treatment is carried out using a wet stretching method in a stretching solution containing 3.0-8.0% boric acid, with a stretching ratio of 4-7 times.
[0021] Furthermore, in the swelling step, the swelling solution contains 0.2-0.8% boride to initially crosslink the substrate; the dyeing solution also contains 0.1-2.0% sodium sulfate as a dyeing aid.
[0022] Furthermore, the process also includes the steps of coating an anti-glare layer, an antistatic layer, a scratch-resistant layer, or attaching a phase retardation film to the surface of the obtained color polarizer.
[0023] Application of a color polarizer as described above in display devices, optical instruments, or goggles.
[0024] Furthermore, the color polarizer is used in vehicle displays, outdoor LCD TVs, outdoor testing equipment, projectors, or marine instruments; after aging in a high temperature and high humidity environment of 85℃ and 85%RH for 1000 hours, the color polarizer shows no bubbles, no delamination, no fading, and the color difference is within the acceptable range.
[0025] Furthermore, the color polarizer is applied to optical systems that require control of specific polarization bands. By adjusting the type and concentration of dichroic dyes, it can cut off light of a specific wavelength while maintaining high transmittance in other bands, thereby improving light utilization efficiency.
[0026] Furthermore, the color polarizer is applied in the field of flexible displays or 3D glasses, utilizing the excellent toughness of PETG or PVA substrates to improve the service life of the product under bending or impact conditions.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention proposes a color polarizer and its preparation method. By selecting a dichroic dye system, the absorption band of the polarizer can be precisely controlled. The product can achieve high polarization degree (>99%) within a specific wavelength range while maintaining high transmittance in other bands. Compared with the traditional method of stacking color-tuning films, the color polarizer prepared by this invention reduces light absorption loss and significantly improves overall transmittance and light utilization efficiency, making it particularly suitable for optical systems requiring specific spectral cutoff or anti-reflection.
[0028] Second, the melt extrusion method (dry method) proposed in this invention is a further optimization based on the traditional melt extrusion process. The resulting color polarizer has excellent weather resistance and durability, as well as high light utilization and polarization performance in specific wavelength bands. Compared with the wet process, it avoids the problems of a large number of water washing, dyeing, and waste liquid treatment steps, significantly shortens the process flow, reduces production costs, and reduces the discharge of organic waste liquid from the source, which is in line with the development trend of green manufacturing.
[0029] Third, the melt extrusion method (dry method) proposed in this invention can prepare polarizing plates of different thicknesses ranging from micrometers to millimeters, meeting the diverse needs of ultra-thin flexible displays or thick rigid optical components. Simultaneously, by adjusting the dye formulation, a rich variety of colors (red, yellow, blue, black, gray, and mixed colors) can be achieved, satisfying diverse personalized customization needs and offering advantages such as flexible and adjustable product form and wide applicability.
[0030] IV. This invention proposes a color polarizer and its preparation method. The prepared color polarizer exhibits excellent high-temperature and high-humidity resistance. For example, TAC color polarizers obtained by wet dyeing and color polarizers prepared based on PC substrates, after being aged for 1000 hours in a harsh environment of 85℃ and 85%RH, show no bubbles, no delamination, no fading, and minimal color difference (e.g., low values of ΔL, Δa, and Δb). This overcomes the defects of traditional iodine-based polarizers, which are prone to decomposition and failure under high temperature and high humidity, and greatly expands the application range of polarizers in high-end fields such as automotive displays and outdoor instruments.
[0031] V. In this invention, the selection of substrates is optimized for different application scenarios: for example, the high heat resistance of PC material is used to solve the weather resistance problem; the low-temperature processing characteristics of PETG material are used to protect the stability of dyes and give the product excellent toughness; the interface reflection loss problem of multi-layer composite structures is solved by refractive index matching technology, thereby further improving the optical performance of polarizers. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the stacked structure of the color polarizer without functional layer in Examples 1 and 2, wherein: 1, protective film; 2, color polarizer layer; 3, release film.
[0033] Figure 2 This is a schematic diagram of the stacked structure of the color polarizer with functional layer in Examples 1 and 2, wherein: 1, protective film; 2, functional layer; 3, color polarizer layer; 4, release film.
[0034] Figure 3 This is a schematic diagram of the stacked structure of the color polarizer without functional layer in Example 3, wherein: 1, protective film; 2, color-tuning PMMA protective layer; 3, iodine-based polarizing layer; 4, PMMA protective layer; 5, release film.
[0035] Figure 4 This is a schematic diagram of the stacked structure of the color polarizer with functional layer in Example 3, wherein: 1, protective film; 2, functional layer; 3, color-tuning PMMA protective layer; 4, iodine-based polarizing layer; 5, PMMA protective layer; 6, release film.
[0036] Figure 5 This is a schematic diagram of the stacked structure of the color polarizer without functional layer in Example 4, wherein: 1, protective film; 2, outer protective film of TAC; 3, dye polarizer film; 4, inner protective film of TAC; 5, release film.
[0037] Figure 6 This is a schematic diagram of the stacked structure of the color polarizer with functional layer in Example 4, wherein: 1, protective film; 2, functional layer; 3, TAC outer protective film; 4, dye polarizer film; 5, TAC inner protective film; 6, release film. Detailed Implementation
[0038] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0039] In this invention, resins that can be used as polarizing film materials include: polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), cellulose triacetate (TAC), polypropylene (PP), cyclic olefin polymer (COP), polyethylene terephthalate (PET), polycarbonate (PC), amorphous polyethylene terephthalate (APET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene terephthalate-1,4-cyclohexanediethanol (PETG), polyethylene terephthalate-1,4-cyclohexanediethanol (PCTG), cyclic olefin copolymer (COC), polyacrylate (PA), polystyrene (PS), polyethersulfone (PES), polyethylene (PE), thermosetting thiourethane, polyurethane (PU), thermoplastic polyurethane (TPU), silicone resin, modified epoxy resin, etc.
[0040] In this invention, dichroic dyes are classified according to their chemical structure, including azo dyes, anthraquinone dyes, etc.; the colors of dichroic dyes include: single colors and colors obtained by mixing two or more dyes.
[0041] To ensure thorough melting and mixing of the dichroic dye and resin, and to prevent yellowing of the raw materials, dispersants and antioxidants need to be added; among them: Dispersants directly affect the dispersion uniformity of dichroic dyes. Uneven dispersion can affect the haze, transmittance, and polarization of the polarizer. Suitable dispersants include: organosilicon dispersants (such as dimethylsiloxane and organosilicon resin microspheres), BKY series dispersants, and phosphate ester dispersants.
[0042] Antioxidants: These are used to capture free radicals generated at high temperatures, preventing dye molecular chains from breaking or changing color, and preventing substrate degradation and yellowing. Suitable antioxidants include hindered phenols (such as 1010, 1076, etc.) and phosphites (such as 168, etc.).
[0043] Example 1 In this embodiment, a color polarizing film is prepared using modified polycarbonate resin (modified PC) as the substrate and by melt stretching method.
[0044] The modified PC has a melt flow index (MFR) greater than 15 g / 10 min and a glass transition temperature (Tg) of 120~145℃. PC resin has high transparency, excellent toughness and impact resistance, and is resistant to high temperature and humidity, making it a good substrate for preparing polarizers by melt stretching.
[0045] The specific preparation method includes the following steps: S1. Drying: Dry the PC resin at 115℃ for 4.5 hours to ensure a moisture content of less than 0.02%.
[0046] In this step, PC resin is highly hygroscopic. The presence of moisture can cause the material to hydrolyze at high temperatures, producing bubbles and silver streaks, and can also damage the material's strength and transparency, affecting the quality of the polarizer. Therefore, PC resin needs to be dried. The drying temperature should be controlled at 110-120℃, and the drying time should be more than 4 hours to ensure that the moisture content is below 0.02%.
[0047] S2. Melting: Melting and mixing are carried out using a twin-screw extruder. PC resin is melt-mixed with dichroic dyes, dispersants, and antioxidants. The temperature gradient from the feed section to the die head is set at 210~250℃, and the die head temperature is controlled at 220~250℃.
[0048] In this embodiment, the amount of dichroic dye used is 0.5-5.0% by weight of PC resin, and the dichroic dye is added according to the formulation of each group in Table 1.
[0049] In this embodiment, the amount of dispersant - dimethylsiloxane is 0.3%, and the amount of antioxidant - hindered phenol 1010 is 0.4%.
[0050] In this step, the filler amounts, based on the weight percentage of PC resin, are as follows: dichroic dye: 0.5~5.0%, dispersant: 0.2~0.5%, antioxidant: 0.3~0.5%. The temperature gradient from the feed section to the die head is set at 210~250℃, and the die head temperature is controlled at 220~250℃ to ensure good melt flowability and achieve uniform dye dispersion.
[0051] S3. Extrusion calendering: The feed rate is metered and adjusted according to the required thickness of the final product; 3 calendering rollers are used, the temperature of the calendering rollers is 110℃, the linear speed is 5 m / min, and the thickness of the unstretched film in the calendering process is 300μm.
[0052] In this step, a single-channel co-extrusion die with an independent flow channel temperature and pressure control system is used. A high-precision gear pump precisely controls the volumetric flow rate, and the feed rate can be metered and adjusted according to the required thickness of the final product.
[0053] During calendering, three calendering rollers (width: 2.3m, diameter: 450mm) are used. The temperature of the calendering rollers is lower than the glass transition temperature (Tg) of PC resin. After the molten material passes through the calendering rollers, it can quickly pass through the Tg point and solidify, maintaining the initial layered structure. The temperature of the calendering rollers is 100~120℃, the linear speed is controlled at 4~6m / min, and the thickness of the unstretched film in the calendering process is controlled at 200~400μm, but can also be controlled according to the thickness required for the final product.
[0054] S4, Stretching: 1) Preheating: The calendered film is preheated through 8 preheating rollers. The preheating temperature is adjusted in steps: 114℃, 118℃, 122℃, 126℃, 130℃, 134℃, 138℃, and 142℃. The linear speed is controlled at 5 m / min.
[0055] 2) Stretching: The preheated film is stretched through two stretching rollers. The stretching temperature is 145℃, and the stretching ratio is controlled by adjusting the linear speed. The thickness of the stretched color polarizing film is 60μm.
[0056] 3) Cooling: The stretched film is cooled by six cooling rollers with the cooling temperature adjusted in steps: 130℃, 120℃, 110℃, 100℃, 90℃, and 80℃.
[0057] In this step, during preheating, the calendered film is preheated through 8 preheating rollers (taking a preheating roller with a width of 2.3m and a diameter of 300mm as an example). The preheating temperature is controlled at 120~150℃, and a stepped preheating method is adopted. The linear speed is controlled at 4~6m / min.
[0058] During stretching, the preheated film is stretched through two stretching rollers (taking a stretching roller with a width of 2.3m and a diameter of 200mm as an example). The stretching temperature is 130~160℃, and the stretching ratio is controlled by adjusting the linear speed: 4~7 times.
[0059] Cooling: The stretched film is cooled by six cooling rollers (taking a cooling roller with a width of 2.3m and a diameter of 300mm as an example) at a temperature of 70~100℃, using a stepped cooling method.
[0060] S5. Heat setting: Hot air setting is achieved using a tenter frame. Temperature control of the tenter frame: preheating section temperature is controlled at 100~120℃; setting section temperature is controlled at 150℃; cooling section temperature is controlled at 40~60℃.
[0061] In this step, the heat setting operation mainly eliminates the internal stress of the film, prevents shrinkage deformation, improves dimensional stability, and enhances physical and mechanical properties. A tenter frame is used for hot air setting, with the temperature control parameters as follows: preheating section: 100~120℃; setting section: 130~160℃; cooling section: 40~60℃.
[0062] S6. Applying a protective film: After heat setting, one side of the color polarizing film is coated with pressure-sensitive adhesive, with a thickness of 30μm, and then a release film is laminated on it; the other side is laminated with a PE protective film. The product's layered structure is as follows: Figure 1 .
[0063] In this step, the thickness of the pressure-sensitive adhesive should generally be controlled between 20 and 40 μm.
[0064] Furthermore, the difference between group 10 and the other groups in this embodiment is that the amount of yellow dye used is 1.25%, and anti-glare treatment is performed on the color polarizer, and amorphous silicone with an average particle size of less than 5μm is coated to obtain an anti-glare color polarizer. The product's layered structure is as follows: Figure 2 .
[0065] test.
[0066] The optical performance of the prepared color polarizers was tested, and the results are shown in Table 1. Comparison group 1 used commercially available iodine-based polarizers for optical performance testing. Simultaneously, the prepared color polarizers underwent high temperature and high humidity (85℃*85%*1000h) testing, and the specific test results are shown in Table 2. The criteria for passing the high temperature and high humidity test were: no bubbles, no wrinkles, no warping, no delamination, and no fading failure.
[0067] Table 1: Test results of product optical performance.
[0068]
[0069] Table 2: Product durability test results.
[0070]
[0071] The results of the above investigation show that the color polarizer products prepared by the method of this embodiment have excellent performance and flexible thickness specifications (from micrometer to millimeter). They not only have good impact resistance, thermoformability, chemical resistance and durability, but also can produce polarizers of specific wavelengths or different colors as needed, effectively improving the light utilization efficiency and transmittance in the 400~700nm wavelength band.
[0072] In terms of process, the melt extrusion method was adopted to replace the traditional wet stretching method, which successfully simplified the production process and reduced costs and environmental pollution, while enabling the preparation of products of different thicknesses.
[0073] In this embodiment, a functional layer can be superimposed on the prepared color polarizer according to the needs of different application scenarios to improve the performance of the polarizer.
[0074] The specific method is as follows: 1. Anti-glare and low reflection: Using a surface coating method, a hardened resin (such as multifunctional acrylic, polyurethane, high acid value resin, etc.) is mixed with micron-sized or nano-sized matting particles (such as silica, nano-alumina) and low-reflection optical materials (such as hollow particles, fluoropolymers, etc.), and then coated on a polarizing film. After drying and UV curing, a coating with dual functions of anti-glare and low reflection is formed.
[0075] 2. Antistatic: To improve the antistatic effect of polarizers, a coating process can be used. The hardening resin (such as acrylic), conductive polymer (such as PEDOT:PSS), adhesive (such as waterborne polyurethane), wetting agent (such as polyether modified siloxane), and solvent (such as water, isopropanol, etc.) are mixed in proportion, and the pH is controlled at 8~10 to ensure the stability of the dispersion. Then, the coating solution is evenly applied to the polarizer film, and the coating thickness is controlled at 0.1~5μm. Finally, it is dried and cured to form an antistatic coating.
[0076] 3. Scratch-resistant coating: Using a surface coating method, hardened resins (such as multifunctional acrylics, polyurethanes, high acid value resins, etc.) are mixed with nanofillers (such as nano silica, nano alumina, graphene oxide, nano siloxanes, polysilazanes, polycrystalline silicon, etc.) in a certain proportion, and then coated on a polarizing film. After drying and UV curing, a scratch-resistant coating is formed to meet the requirements of different hardnesses (such as 1H, 2H, 3H, etc.).
[0077] 4. Lamination with Phase Retardation Film: Polarizers themselves only produce linearly polarized light, while phase retardation films (λ / 4 films) can change the polarization state of light. When the two are laminated at a specific angle, linearly polarized light can be converted into circularly polarized light. This allows ambient light entering the screen to be reflected, causing its polarization direction to rotate by 90°, thus being blocked by the polarizer and unable to escape. This greatly reduces reflected light, making the screen still visible under strong light. Phase retardation films can include PMMA films, TAC films, COP films, PET films, etc.
[0078] Example 2 In this embodiment, polyethylene terephthalate-1,4-cyclohexanediol ester (PETG) is used as the substrate to prepare color polarizing film using the melt stretching method. PETG resin has a glass transition temperature (Tg) of 75~85℃. PETG resin has extremely high transparency, excellent toughness and impact resistance, good chemical resistance, and is very easy to process, making it a good substrate for preparing polarizing film by the melt stretching method.
[0079] The specific preparation method includes the following steps: S1. Drying: Dry the PETG resin at 70℃ for 4 hours to ensure a moisture content of less than 0.02%.
[0080] In this step, PETG resin is highly hygroscopic. The presence of moisture can cause the material to hydrolyze at high temperatures, producing bubbles and silver streaks, and easily damaging the material's strength and transparency, thus affecting the quality of the polarizer. Therefore, PETG resin needs to be dried. The drying temperature should be controlled between 65 and 75°C, and the drying time should be more than 4 hours to ensure that the moisture content is below 0.02%.
[0081] S2. Melting: Melting and mixing are carried out using a twin-screw extruder. PETG resin is melt-mixed with dichroic dyes, dispersants, and antioxidants. The temperature gradient from the feed section to the die head is set at 180~220℃, and the die head temperature is controlled at 200~220℃.
[0082] In this embodiment, the amount of dichroic dye used is 0.5-5.0% by weight percentage of PETG resin, and the dichroic dye is added according to the formulations of each group in Table 3.
[0083] In this embodiment, the amount of dispersant - dimethylsiloxane is 0.3%, and the amount of antioxidant hindered phenol 1010 is 0.4%.
[0084] In this step, the filler amounts, based on the weight percentage of PETG resin, are as follows: dichroic dye: 0.5~5.0%, dispersant: 0.2~0.5%, antioxidant: 0.3~0.5%. The temperature gradient from the feed section to the die head is set at 180~220℃, and the die head temperature is controlled at 200~220℃ to ensure good melt flowability and achieve uniform dye dispersion.
[0085] S3. Extrusion calendering: The feed rate is metered and adjusted according to the required thickness of the final product; 3 calendering rollers are used, the temperature of the calendering rollers is 70℃, the linear speed is 5 m / min, and the thickness of the unstretched film in the calendering process is 300μm.
[0086] In this step, a single-channel co-extrusion die with an independent flow channel temperature and pressure control system is used. A high-precision gear pump precisely controls the volumetric flow rate, and the feed rate can be metered and adjusted according to the required thickness of the final product.
[0087] During calendering, three calendering rollers (width: 2.3m, diameter: 450mm) are used. The temperature of the calendering rollers is lower than the glass transition temperature (Tg) of PETG resin. After the molten material passes through the calendering rollers, it can quickly pass through the Tg point and solidify, maintaining the initial layered structure. The temperature of the calendering rollers is 65~75℃, the linear speed is controlled at 4~6m / min, and the thickness of the unstretched film in the calendering process is controlled at 200~400μm, but can also be controlled according to the thickness required for the final product.
[0088] S4, Stretching: 1) Preheating: The calendered film is preheated through 8 preheating rollers. The preheating temperature is adjusted in steps: 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, and the linear speed is controlled at 5 m / min.
[0089] 2) Stretching: The preheated film is stretched through two stretching rollers. The stretching temperature is 110℃, and the stretching ratio is controlled by adjusting the linear speed. The thickness of the stretched color polarizing film is 60μm.
[0090] 3) Cooling: The stretched film is cooled by six cooling rollers with the cooling temperature adjusted in steps: 100℃, 90℃, 80℃, 70℃, 65℃, and 60℃.
[0091] In this step, during preheating, the calendered film is preheated through 8 preheating rollers (taking a preheating roller with a width of 2.3m and a diameter of 300mm as an example). The preheating temperature is controlled at 90~120℃, and a stepped preheating method is adopted. The linear speed is controlled at 4~6m / min.
[0092] During stretching, the preheated film is stretched through two stretching rollers (taking a stretching roller with a width of 2.3m and a diameter of 200mm as an example). The stretching temperature is 100~130℃, and the stretching ratio is controlled by adjusting the linear speed: 4~7 times.
[0093] Cooling: The stretched film is cooled by six cooling rollers (taking a cooling roller with a width of 2.3m and a diameter of 300mm as an example) at a temperature of 40~70℃, using a stepped cooling method.
[0094] S5. Heat setting: Hot air setting is achieved using a tenter frame. Temperature control of the tenter frame: preheating section temperature is controlled at 70~90℃; setting section temperature is controlled at 120℃; cooling section temperature is controlled at 40~60℃.
[0095] In this step, the heat setting operation mainly eliminates the internal stress of the film, prevents shrinkage deformation, improves dimensional stability, and enhances physical and mechanical properties. A tenter frame is used for hot air setting, with the temperature control parameters as follows: preheating section: 70~90℃; setting section: 100~130℃; cooling section: 40~60℃.
[0096] S6. Applying a protective film: After heat setting, one side of the color polarizing film is coated with pressure-sensitive adhesive, with a thickness of 30μm, and then a release film is laminated on it; the other side is laminated with a PE protective film. The product's layered structure is as follows: Figure 1 .
[0097] In this step, the thickness of the pressure-sensitive adhesive should generally be controlled between 20 and 40 μm.
[0098] Furthermore, the difference between group 10 and the other groups in this embodiment is that the amount of yellow dye used is 1.25%, and anti-glare treatment is performed on the color polarizer, and amorphous silicone with an average particle size of less than 5μm is coated to obtain an anti-glare color polarizer. The product's layered structure is as follows: Figure 2 .
[0099] In this embodiment, depending on the needs of different application scenarios, a functional layer can also be superimposed on the prepared color polarizer to improve the performance of the polarizer. The specific operation method is the same as in Embodiment 1.
[0100] test.
[0101] The optical performance of the prepared color polarizers was tested, and the test results are shown in Table 3. The optical performance of the control group 1 was tested using commercially available iodine-based polarizers.
[0102] Table 3: Test results of product optical performance.
[0103]
[0104] The results of the above investigation show that the color polarizer products prepared by the method of this embodiment have excellent performance and flexible thickness specifications (from micrometer to millimeter). They not only have good impact resistance, thermoforming properties and chemical resistance, but also can produce polarizers of specific wavelengths or different colors as needed, effectively improving the light utilization efficiency and transmittance in the 400~700nm wavelength band.
[0105] In terms of process, the melt extrusion method was adopted to replace the traditional wet stretching method, which successfully simplified the production process and reduced costs and environmental pollution, while enabling the preparation of products of different thicknesses.
[0106] In this embodiment, a functional layer can be superimposed on the prepared color polarizer according to the needs of different application scenarios to improve the performance of the polarizer.
[0107] The color polarizer obtained by the preparation method of this embodiment has the characteristics of high temperature and high humidity resistance, ultra-thinness, and multiple colors. It can be used in precision fields such as LCD displays, polarized sunglasses, OLED displays, 3D glasses, outdoor LCD TVs, vehicle control systems, projectors, outdoor testing instruments, marine instruments, and medical equipment.
[0108] Example 3 In this embodiment, a color polarizer is used as an example to further illustrate this solution.
[0109] Specifically, the structural reference of color polarizers Figure 3 , 4 .in, Figure 3 The diagram illustrates the product stack-up structure without functional layers. The color polarizer includes a protective film 1, a color-correcting PMMA protective layer 2, an iodine-based polarizing layer 3, a PMMA protective layer 4, and a release film 5. Figure 4 The diagram illustrates the product's stacked structure with functional layers. The color polarizer includes a protective film 1, a functional layer 2, a color-tuning PMMA protective layer 3, an iodine-based polarizing layer 4, a PMMA protective layer 5, and a release film 6. The functional layers are stacked according to the needs of different application scenarios, and their preparation method is the same as in Example 1.
[0110] In this embodiment, the iodine-based polarizing layer is made of polyvinyl alcohol (PVA) resin. Given that PVA resin has excellent iodine alignment capabilities, it is suitable as a polarizing layer material for polarizing films. Preferably, the glass transition temperature of the PVA resin is between 75 and 85°C, the degree of saponification is above 99.8 mol%, and the degree of polymerization ranges from 1500 to 6000.
[0111] The dyes in the iodine-based polarizing layer include iodine, potassium iodide, and boric acid. To ensure uniform dispersion of iodine, potassium iodide, and boric acid with PVA, they should be thoroughly dissolved and mixed before being melt-mixed with PVA resin. However, water cannot be used in the melt extrusion process. Therefore, one or more substances such as glycerol, diglycerol, and triglycerides are used to replace water. Glycerol, diglycerol, and triglycerides also act as plasticizers, reducing melt viscosity and preventing the PVA resin from overheating and decomposing.
[0112] In this embodiment, the color-correcting protective layer not only protects the iodine-based polarizing layer but also has a color-correcting function. Suitable resins that are easy to align with dyes include polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polycarbonate (PC), and polyethylene terephthalate-1,4-cyclohexanediethanol (PETG).
[0113] Since iodine-based polarizing layers typically use PVA resin with a refractive index of 1.50, while PMMA resin has a refractive index of 1.49, their refractive indices are highly matched, effectively reducing light refraction at the interlayer interface. Simultaneously, PMMA resin exhibits a light transmittance of over 93% and demonstrates good water resistance, heat resistance, mechanical properties, and processability. Therefore, PMMA resin is preferred as the tinting and protective layer for iodine-based polarizing layers. In this embodiment, polymethyl methacrylate (PMMA) is selected as the substrate to prepare the tinting protective layer; preferably, the glass transition temperature (Tg) of PMMA is in the range of 105~120℃.
[0114] In this embodiment, the dye used in the color-tuned PMMA protective layer is the aforementioned dichroic dye.
[0115] In this embodiment, the PMMA protective layer is used to protect the iodine-based polarizing layer.
[0116] The specific preparation method is as follows: S1. Drying: Dry the PMMA resin at 90℃ for 4 hours; dry the PVA resin (degree of polymerization: 2400, degree of saponification: 99.9 mol%) at 70℃ for 4 hours, ensuring that the moisture content of both is below 0.02%.
[0117] In this step, considering that PMMA and PVA resins, if containing moisture during high-temperature melt extrusion, are prone to defects such as bubbles and silver streaks, thereby damaging the mechanical strength and optical transparency of the materials and reducing the quality of the polarizer, a drying pretreatment is required for the above resins. Preferably, the drying conditions for PMMA resin are 85~95℃ for at least 4 hours, and the drying conditions for PVA resin are 60~70℃ for at least 4 hours; after treatment, the moisture content of both resins should be strictly controlled below 0.02%.
[0118] S2, Melting: Melting and mixing are carried out using a twin-screw extruder.
[0119] Iodine-based polarizing layer: First, a mixed solution containing iodine, potassium iodide, boric acid, and glycerol is prepared. The amount of iodine added is 2.0% by weight of glycerol, the amount of potassium iodide added is 20%, and the amount of boric acid added is 2.0%, with the dissolution temperature controlled at 45°C. Subsequently, the above mixed solution is melt-blended with PVA resin at high temperature; the amount of the mixed solution added is 20% by weight of PVA resin. During melt extrusion, the temperature gradient from the feed section to the die head is set to 170~200°C, and the temperature in the die head area is controlled at 180~200°C.
[0120] In this step, the preparation method of the iodine-based polarizing layer can be adjusted appropriately according to requirements. When preparing the dye, the amount of iodine added is 1-3% by weight of glycerol, the amount of potassium iodide added is 10-30%, and the amount of boric acid added is 1-3%. The dissolution temperature is controlled at 30-60℃. When the dye mixture solution is melt-mixed with PVA resin through a twin-screw extruder, the amount of dye mixture solution used is 15-30% by weight of PVA resin.
[0121] Tinted PMMA Protective Layer: PMMA is melt-mixed with dichroic dyes, dispersants, and antioxidants. The temperature gradient from the feed section to the die head is set at 180~210℃, and the die head temperature is controlled at 190~210℃. The dichroic dye is added at a rate of 0.5~5.0% by weight of PMMA resin, according to the formulations in Table 4. The dispersant—dimethylsiloxane—is added at 0.3%, and the antioxidant—hindered phenol 1010—is added at 0.4%.
[0122] In this step, the preparation method of the tinted PMMA protective layer can be adjusted appropriately according to requirements. When PMMA resin is melt-mixed with dichroic dyes, dispersants, and antioxidants, the amount of each filler, based on the weight percentage of PMMA resin, is as follows: dichroic dye: 0.5~5.0%, dispersant: 0.2~0.5%, antioxidant: 0.3~0.5%. Simultaneously, the melt mixing temperature is adjusted, with the temperature gradient from the feed section to the die head set at 180~210℃, and the die head temperature controlled at 190~210℃ to ensure melt flowability and achieve uniform dye dispersion.
[0123] PMMA protective layer: The temperature gradient from the feed section to the die head is set to 180~210℃, and the temperature in the die head area should be controlled at 190~210℃ to ensure melt flowability.
[0124] S3. Extrusion Calendering: The tinted PMMA protective layer, iodine-based polarizing layer, and PMMA protective layer are co-extruded in a 1:1:1 thickness ratio. The feed amount of each layer is metered and adjusted according to the required thickness of the final product. Three calendering rollers are used. The temperature of the calendering rollers is 90℃, the linear speed is 5 m / min, and the thickness of the unstretched film in the calendering process is 300μm.
[0125] In this step, a multi-channel co-extrusion die with an independent flow channel temperature and pressure control system is used to achieve multi-layer co-extrusion. The volumetric flow rate of each layer—the tinted PMMA protective layer, the iodine-based polarizing layer, and the PMMA protective layer—is precisely controlled by a high-precision gear pump, and the feed rate can be metered and adjusted according to the required thickness of the final product. Suitablely, the iodine-based polarizing layer thickness is 5~25μm; the tinted PMMA protective layer and the PMMA protective layer thickness are 10~50μm.
[0126] During calendering, three calendering rollers (2.3m wide, 450mm in diameter) are used. The temperature of the calendering rollers must be lower than the glass transition temperature (Tg) of PMMA resin. After the molten material passes through the calendering rollers, it can quickly pass through the Tg point and solidify, maintaining the initial layered structure. The temperature of the calendering rollers is 80~100℃, and the linear speed is controlled at 4~6 m / min. The thickness of the unstretched film in the calendering process is controlled at 200~400μm, but it can also be controlled according to the thickness required for the final product.
[0127] S4, Stretching: 1) Preheating: The unstretched film after calendering is preheated through 8 preheating rollers. The preheating temperature is adjusted in steps: 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, and 135℃. The linear speed is controlled at 5 m / min.
[0128] 2) Stretching: The preheated film is stretched through two stretching rollers. The stretching temperature is 135℃, and the stretching ratio is controlled by adjusting the linear speed. The thickness of the stretched color polarizing film is 60μm.
[0129] 3) Cooling: The stretched film is cooled by six cooling rollers with the cooling temperature adjusted in steps: 120℃, 110℃, 100℃, 90℃, 80℃, and 70℃.
[0130] In this step, during preheating, the calendered film is preheated through 8 preheating rollers (taking a preheating roller with a width of 2.3m and a diameter of 300mm as an example). The preheating temperature is controlled at 110~150℃, and a stepped preheating method is adopted. The linear speed is controlled at 4~6m / min.
[0131] During stretching, the preheated film is stretched through two stretching rollers (taking a stretching roller with a width of 2.3m and a diameter of 200mm as an example). The stretching temperature is 120~160℃, and the stretching ratio is controlled by adjusting the linear speed: 4~7 times.
[0132] Cooling: The stretched film is cooled by six cooling rollers (taking a cooling roller with a width of 2.3m and a diameter of 300mm as an example) at a temperature of 60~100℃, using a stepped cooling method.
[0133] S5. Heat setting: Hot air setting is achieved using a tenter frame. Temperature control of the tenter frame: preheating section temperature is controlled at 80~100℃; setting section temperature is controlled at 140℃; cooling section temperature is controlled at 40~60℃.
[0134] In this step, the heat setting operation mainly eliminates the internal stress of the film, prevents shrinkage deformation, improves dimensional stability, and enhances physical and mechanical properties. A tenter frame is used for hot air setting, with the temperature control parameters as follows: preheating section: 80~100℃; setting section: 120~160℃; cooling section: 40~60℃.
[0135] S6. Protective Film Application: After heat setting, a tinted PMMA protective layer is coated with pressure-sensitive adhesive, 30μm thick, and then a release film is laminated onto it; the PMMA protective layer is then laminated with a PE protective film. The product's layered structure is as follows: Figure 3 .
[0136] In this step, the thickness of the pressure-sensitive adhesive should generally be controlled between 20 and 40 μm.
[0137] Furthermore, the difference between group 9 and the other groups in this embodiment is that the amount of yellow dye used is 1.25%, and an anti-glare treatment is performed on the tinted PMMA protective layer. Amorphous silicone with an average particle size of less than 5μm is then coated to obtain an anti-glare color polarizer. The product's layered structure is as follows: Figure 4 .
[0138] test.
[0139] The optical performance of the prepared color polarizers was tested, and the test results are shown in Table 4. The optical performance of the control group 1 was tested using commercially available iodine-based polarizers.
[0140] Table 4: Test results of product optical performance.
[0141]
[0142] Based on the above investigation results, it can be seen that the color polarizer prepared in this embodiment (the color layer of the polarizer is prepared by melting and mixing PMMA material and dichroic dyes) significantly reduces the overall thickness of the product by reducing the number of individual color toning layers, thus broadening its application scenarios, compared with the traditional tunable high polarizer. At the same time, the solution adopts a melt extrusion integrated molding process, which effectively simplifies the production process, reduces production costs, and reduces environmental pollution.
[0143] Example 4 In this embodiment, a wet method for preparing a color polarizer is used as an example to further illustrate this solution.
[0144] In this wet thin film preparation process, the substrate for preparing the color polarizer can be selected from polyvinyl alcohol resin (PVA), polyvinyl alcohol formaldehyde (PVF), polyvinyl alcohol acetal, as well as PVA modified with olefins such as ethylene and propylene, PVA modified with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid and their esters, PVA modified with acrylamide, PVA modified with acetyl or acetyl groups, or PVA modified with carboxyl groups, etc.
[0145] This embodiment uses polyvinyl alcohol resin as a substrate to prepare a dye polarizing film as an example to further illustrate the present invention. During the preparation process, plasticizers, surfactants, and other additives can also be added. Specifically, as plasticizers, glycerol, diglycerol, triglycerides, ethylene glycol, propylene glycol, polyethylene glycol, etc., can be selected, with an addition amount of 5-15%; as surfactants, sodium dodecyl sulfate (SDBS), sodium dodecyl sulfate (SDS), polyoxyethylene sodium dodecyl sulfate, diethanolamide laurate, etc., can be selected, with an addition amount of 0.01-0.1%.
[0146] In addition, the substrate can also be a commercially available polyvinyl alcohol (PVA) film. Preferably, the degree of polymerization of the polyvinyl alcohol resin is 1500~6000.
[0147] Structural reference of a color polarizer (without functional layer) Figure 5It comprises a five-layer stacked structure, including a protective film 1, a TAC outer protective film 2, a dye polarizing film 3, a TAC inner protective film 4, and a release film 5. Another structural reference for a color polarizer with functional layers is provided. Figure 6 It includes a protective film 1, a functional layer 2, a TAC outer protective film 3, a dye polarizing film 4, a TAC inner protective film 5, and a release film 6. The functional layers are stacked according to the needs of different application scenarios, and the preparation method is the same as in Example 1.
[0148] The specific steps are as follows: S1. Water washing: Commercially available polyvinyl alcohol optical film (degree of polymerization: 2400, thickness: 70μm) was selected as the substrate. First, the PVA substrate was placed in a water washing tank for cleaning, with the water temperature controlled at 30℃ and the washing time at 120s.
[0149] In this step, the PVA substrate is immersed in a washing solution to remove impurities such as dust, anti-blocking agents, and plasticizers adhering to the film surface. The washing solution is preferably pure water or deionized water. Generally, the washing temperature can be controlled between 20 and 50°C, and the washing time is within the range of 60 to 240 seconds.
[0150] S2, Swelling: The PVA substrate after washing is immersed in a swelling bath containing 0.3% boric acid solution for treatment. The temperature is controlled at 30℃ and the swelling time is 120s.
[0151] In this step, the polyvinyl alcohol (PVA) film is fully swollen, thereby improving the efficiency of subsequent stretching and the uniformity of dyeing. A small amount of glycerol or potassium iodide can be added to the swelling solution to improve processing performance; alternatively, 0.2-0.8% boride can be added. The small amount of boride reacts with the polyhydroxyl structures in PVA to form a preliminary cross-linking reaction, enhancing structural stability and thus aiding the dyeing process. Generally, the swelling temperature is controlled at 20-50℃, the swelling time at 60-240s, and the swelling degree is preferably controlled at 1.1-1.5.
[0152] S3. Dyeing: The swollen PVA base film is immersed in a dyeing bath containing a dyeing solution for dyeing treatment. The main purpose of this step is to ensure that the dye is fully adsorbed into the substrate. The colored dyes are classified according to their chemical structure, including azo dyes, anthraquinone dyes, etc.; the dyes can be used alone or by adjusting the ratio of different dyes to obtain the desired color or specific absorption band.
[0153] In this embodiment, the dyeing solution is based on deionized water at a weight percentage of 100%, and the amount of dichroic dye is 0.01-3%, added according to the formulations of each group in Table 5. The concentration of sodium sulfate as a dyeing auxiliary is 0.5%; the process parameters are controlled as follows: dyeing temperature 30℃, dyeing time 60s.
[0154] Generally, the concentration of the staining solution is controlled at 0.01-3% by weight of deionized water, preferably 0.75-1.5%. The staining temperature range is 20-40℃, and the staining time range is 30-240s.
[0155] In addition, dyeing auxiliaries can be added to the dyeing solution to improve the dyeing effect. Suitable auxiliaries include sodium carbonate, sodium bicarbonate, sodium chloride, sodium sulfate, anhydrous sodium sulfate, and sodium tripolyphosphate; preferably, sodium sulfate is used as the dyeing aid, with a preferred content range of 0.1% to 2.0%.
[0156] S4. Washing: Place the dyed PVA film in a water washing tank for washing, control the water temperature at 30℃, and the washing time is 30s.
[0157] The main purpose of this step is to remove free dye from the substrate surface to prevent it from entering the subsequent crosslinking solution and affecting the process. The washing solution is preferably pure water or deionized water. Generally, the washing temperature is controlled at 20~40℃, and the washing time is controlled at 10~60s.
[0158] S5. Crosslinking: The dyed and washed PVA base film is immersed in a crosslinking tank containing a crosslinking solution for crosslinking treatment. In this embodiment, the crosslinking solution contains 2.0% boric acid, the crosslinking temperature is 30°C, and the crosslinking time is 60 seconds.
[0159] In this step, borides (such as boric acid or borax) are used as crosslinking agents to chemically react with the numerous hydroxyl groups on the polyvinyl alcohol (PVA) molecular chain, forming borate ester bonds, thereby constructing a dense and stable three-dimensional network structure within the film. Generally, based on deionized water as 100% by weight, the boric acid content in the crosslinking solution is 1.0–8.0%; the crosslinking temperature is controlled at 20–50°C, and the crosslinking time is 30–240 s.
[0160] S6. Stretching: The cross-linked PVA base film is placed in a stretching tank for stretching treatment. In this embodiment, a wet stretching method is used, the stretching solution contains 4.0% boric acid, the stretching temperature is controlled at 55°C, the stretching time is 180s, and the stretching ratio is 6.0 times.
[0161] By stretching the dyed and cross-linked substrate, the originally coiled and entangled PVA molecular chains are straightened and oriented along the stretching direction, and the iodine molecules adsorbed on the PVA chains also align accordingly. This arrangement causes light waves with vibration directions parallel to the molecular chains to be strongly absorbed, while light waves with vibration directions perpendicular to the molecular chains can pass through, thus generating polarized light.
[0162] Commonly used stretching methods include dry stretching and wet stretching. In dry stretching, air is preferred as the medium, with the temperature controlled at 20–180°C and the humidity at 20–95%RH. The substrate can be heated by roller heating, infrared heating, or hot air oven heating, etc.; stretching can be done in one stage or multiple stages. In wet stretching, the cross-linked substrate is immersed in a stretching bath containing a stretching solution for stretching. The boric acid content in the stretching solution is 3.0–8.0% (based on 100% deionized water by weight); the stretching temperature is 40–60°C, the stretching time is 120–240 s, and the stretching ratio is 4–7 times.
[0163] It should be noted that the stretching process of the substrate can be performed independently, or it can be pre-stretched during processes such as washing, swelling, and dyeing, followed by the final stretching process. Regardless of the method used, the total stretching ratio of the substrate is controlled between 4 and 7 times.
[0164] S7. Washing: Place the stretched PVA film in a water washing tank for washing, control the water temperature at 30℃, and the washing time is 30s.
[0165] In this step, to remove precipitated dyes, free crosslinking agents, and other impurities adhering to the substrate surface to ensure the optical uniformity and appearance quality of the film, the stretched substrate is immersed in a washing tank containing a washing solution, preferably pure water or deionized water. Generally, the washing temperature is controlled at 20~40℃, and the washing time is preferably 10~60s.
[0166] S8. Drying: The washed PVA film is dried. In this embodiment, the drying temperature is 80°C and the drying time is 5 minutes.
[0167] In this step, drying can be achieved through methods such as forced-air drying, infrared drying, or oven drying. Generally, the drying temperature should be controlled between 60 and 100°C, and the drying time should be between 5 and 10 minutes.
[0168] S9. Laminating Protective Layer: The dried color polarizing film is laminated with the TAC protective film. The product's layered structure is as follows: Figure 5 As shown.
[0169] In this step, the selected protective film must possess good optical transparency, excellent mechanical strength, and resistance to high temperature and humidity, as well as chemical corrosion. Suitable protective film materials include cellulose triacetate (TAC) film, polyethylene terephthalate (PET) film, polymethyl methacrylate (PMMA) film, cyclic olefin polymer (COP, COC) film, and tetrafluoroethylene / hexafluoropropylene copolymer fluorinated film, etc. Preferably, the thickness of the protective film is 30~70 μm. In this embodiment, cellulose triacetate (TAC) film is selected as the protective film.
[0170] In addition, an adhesive layer needs to be provided between the PVA polarizing film and the TAC protective film. The adhesive can be selected from polyvinyl alcohol-based water-based adhesives, acrylic adhesives, polyurethane adhesives, epoxy adhesives, urethane emulsion adhesives, polyester-isocyanate adhesives, etc.
[0171] Furthermore, the difference between group 10 and the other groups in this embodiment is that the amount of yellow dye used is 1.25%, and anti-glare treatment is performed on the TAC protective layer. Amorphous silicone with an average particle size of less than 5μm is then coated to obtain an anti-glare color polarizer. The product's layered structure is as follows: Figure 6 .
[0172] test.
[0173] The optical performance of the prepared color polarizers was tested, and the results are shown in Table 5. Comparison group 1 used commercially available iodine-based polarizers for optical performance testing. Simultaneously, the prepared color polarizers underwent high temperature and high humidity (85℃*85%*1000h) testing, and the specific test results are shown in Table 6. The criteria for passing the high temperature and high humidity test were: no bubbles, no wrinkles, no warping, no delamination, and no fading failure.
[0174] Table 5: Test results of product optical performance.
[0175]
[0176] Table 6: Product durability test results.
[0177]
[0178] As can be seen from the above investigation results, the color polarizer product prepared in this embodiment can produce polarizers of different colors and specific wavelengths according to the requirements, significantly improving the transmittance and light utilization efficiency in the 400~700nm band. At the same time, its high temperature and high humidity resistance is better than that of conventional iodine-based polarizers, and it can adapt to more demanding application environments. This effect is achieved by using wet dyeing process with dyes of different colors.
[0179] In this embodiment, depending on the needs of different application scenarios, a functional layer can be further superimposed on the fabricated color polarizer to improve the overall performance of the polarizer. The specific implementation scheme is as follows: 1. Anti-glare and low-reflection layer: Using a surface coating process, hardened resin (such as multifunctional acrylic, polyurethane, high acid value resin, etc.) is mixed with micron- or nano-sized matting particles (such as silica, nano alumina, etc.) and low-reflection optical materials (such as hollow particles, fluoropolymers, etc.) in a certain proportion and then coated on the surface of the TAC protective layer. After drying and UV curing, a coating with both anti-glare and low-reflection functions is formed.
[0180] 2. Antistatic Layer: To enhance the antistatic properties of the polarizer, a coating process can be used. The curing resin (e.g., acrylic), conductive polymer (e.g., PEDOT:PSS), adhesive (e.g., waterborne polyurethane), wetting agent (e.g., polyether-modified siloxane), and solvent (e.g., water, isopropanol) are mixed uniformly, and the pH of the system is controlled between 8 and 10 to ensure the stability of the dispersion. The coating solution is then uniformly applied to the TAC protective layer, with a coating thickness controlled at 0.1 μm-5 μm. After drying and curing, an antistatic coating is formed.
[0181] 3. Scratch-resistant layer: Using a surface coating method, hardened resin (such as multifunctional acrylic, polyurethane, high acid value resin, etc.) and nanofillers (such as nano silica, nano alumina, graphene oxide, nano siloxane, polysilazane, polycrystalline silicon, etc.) are mixed in a certain proportion and then coated on the TAC protective layer. After drying and UV curing, a scratch-resistant coating is formed to meet the application requirements of different hardness (such as 1H, 2H, 3H, etc.).
[0182] 4. Phase Retardation Film Lamination: A polarizer and a phase retardation film (such as a λ / 4 film) are laminated together. The polarizer only produces linearly polarized light, while the phase retardation film can change the polarization state of light. When the two are bonded at a specific angle, linearly polarized light can be converted into circularly polarized light. This structure allows ambient light entering the screen to be polarized 90° after reflection, thus being blocked by the polarizer and unable to escape, thereby greatly reducing reflected light and maintaining good visibility of the screen in strong light environments. The phase retardation film can be made of PMMA film, TAC film, COP film, PET film, etc.
[0183] In summary, the color dye polarizing film and polarizing plate described in this invention have broad application prospects, covering professional fields such as outdoor LCD TVs, outdoor testing equipment, vehicle-mounted industrial control systems, projectors, marine instruments, and medical equipment. This product is particularly suitable for applications requiring specific control of polarization wavelengths, diverse color reproduction, and operation in harsh environments such as high temperature and high humidity.
[0184] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications or equivalent changes made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A color polarizer, characterized in that, The polarizer includes at least one color polarizing functional layer; The color polarizing functional layer is composed of a resin substrate and a dichroic dye incorporated therein; The dichroic dyes are oriented in a specific direction in the resin substrate, so that the color polarizer has polarization properties in a specific absorption band. The resin substrate is selected from at least one of polyvinyl alcohol, polymethyl methacrylate, cellulose triacetate, polypropylene, cyclic olefin polymers, polyethylene terephthalate, polycarbonate, non-crystalline polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene terephthalate-1,4-cyclohexanediol, polyethylene terephthalate-1,4-cyclohexanediol, cyclic olefin copolymers, polyacrylates, polystyrene, polyethersulfone, polyethylene, thermosetting thiourethane, polyurethane, thermoplastic polyurethane, silicone resin, and modified epoxy resin.
2. The color polarizer according to claim 1, characterized in that: The dichroic dyes are dispersed in the resin substrate by melt mixing to form a single-layer or double-layer composite colored polarizing layer.
3. A color polarizer according to claim 2, characterized in that: The resin substrate is polycarbonate with a melt index greater than 15 g / 10 min and a glass transition temperature of 120~145℃. The color polarizing functional layer is a single-layer structure, and the polarizer shows no bubbles, no delamination, and no fading failure after aging for 1000 hours at 85℃ and 85%RH.
4. A color polarizer according to claim 2, characterized in that: The resin substrate is polyethylene terephthalate-1,4-cyclohexanediol ester, and its glass transition temperature is 75~85℃. The color polarizing functional layer is formed at a low processing temperature of 180~220℃ to reduce dye decomposition.
5. A color polarizer according to claim 2, characterized in that: The color polarizing layer includes a color-tone protective layer and an iodine-based polarizing layer stacked together; The resin substrate of the color-tone protective layer is polymethyl methacrylate; The resin substrate of the iodine-based polarizing layer is polyvinyl alcohol; The absolute value of the difference between the refractive index of the polymethyl methacrylate resin and the refractive index of the polyvinyl alcohol resin is within 0.
01.
6. A color polarizer according to claim 1, characterized in that: The dichroic dye is incorporated into the resin substrate by impregnation and adsorption; the resin substrate is polyvinyl alcohol, and the colored polarizing layer is cross-linked with boric acid.
7. A method for preparing a color polarizer as described in any one of claims 1 to 6, characterized in that, Includes the following steps: I. Provide resin substrate; II. Incorporating dichroic dyes into the resin substrate; III. The resin substrate containing the dichroic dye is stretched to align the dichroic dyes and obtain a color polarizer.
8. The preparation method according to claim 7, characterized in that: In step II, the step of bonding the dichroic dye to the resin substrate is performed using a melt extrusion process: The resin is melt-mixed with dichroic dye, dispersant, and antioxidant, and then co-extruded through an extrusion die to obtain an unstretched film. The stretching process employs a dry stretching method, which involves stretching in a hot air medium with a stretching ratio of 4 to 7 times.
9. The preparation method according to claim 8, characterized in that: When the resin substrate is polycarbonate, the melt temperature gradient is set to 210~250℃ and the stretching temperature is 130~160℃. When the resin substrate is polyethylene terephthalate-1,4-cyclohexanediethanol ester, the melting temperature gradient is set to 180~220℃ and the stretching temperature is 100~130℃.
10. The preparation method according to claim 8, characterized in that: When the resin substrate includes polymethyl methacrylate and polyvinyl alcohol, a multi-channel co-extrusion die is used to co-extrude the tinted PMMA protective layer melt, the iodine-based PVA polarizing layer melt, and the PMMA protective layer melt to form a layered structure.
11. The preparation method according to claim 7, characterized in that: The step of bonding the dichroic dye to the resin substrate employs a wet dyeing process. The resin substrate is polyvinyl alcohol; After the polyvinyl alcohol substrate is washed with water and swelled in sequence, it is immersed in a dyeing solution containing dichroic dyes for dyeing. After staining, a cross-linking treatment is performed, wherein the cross-linking solution used in the cross-linking treatment contains 1.0~8.0% boric acid; The stretching treatment is carried out using a wet stretching method in a stretching solution containing 3.0-8.0% boric acid, with a stretching ratio of 4-7 times.
12. The preparation method according to claim 11, characterized in that: In the swelling step, the swelling solution contains 0.2-0.8% boride, which causes the substrate to undergo initial cross-linking. The dyeing solution also contains 0.1-2.0% sodium sulfate as a dyeing aid.
13. The preparation method according to claim 7, characterized in that, The process also includes the steps of coating an anti-glare layer, an antistatic layer, a scratch-resistant layer, or attaching a phase retardation film to the surface of the prepared color polarizer.
14. The use of a color polarizer as described in any one of claims 1 to 7 in a display device, optical instrument, or goggles.
15. The application according to claim 14, characterized in that: The color polarizer is used in vehicle displays, outdoor LCD TVs, outdoor testing equipment, projectors, or marine instruments. After being aged for 1000 hours in a high-temperature and high-humidity environment of 85℃ and 85%RH, the color polarizer showed no bubbles, no delamination, no fading, and the color difference was within acceptable limits.
16. The application according to claim 14, characterized in that: The color polarizer is used in optical systems that require control of specific polarization bands. By adjusting the type and concentration of dichroic dyes, it can cut off light of a specific wavelength while maintaining high transmittance in other bands.
17. The application according to claim 14, characterized in that: The color polarizer is used in flexible displays or 3D glasses.